Analisis Visual Poster "Kenduri Seni Melayu" Batam: Periode 2022-2024 - Sapitri, Ria; Ramli, Arwin; Lestari Harahap, Widiya (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Cultural posters serve as a primary medium for communicating the identity and values of Malay cultural heritage to the public. However, few in-depth studies have analyzed the changes in visual and formal aspects of posters over the years, particularly in the context of the Kenduri Seni Melayu in Batam, Riau Islands. This research aims to identify and analyze the development of visual and formal elements in the design of the “Kenduri Seni Melayu” posters from 2022 to 2024, as well as to formulate recommendations for enhancing their visual effectiveness. The study employs a qualitative approach with a non-experimental observational design. Official posters from 2022, 2023, and 2024 were analyzed by 54 Visual Communication Design (DKV) students after receiving preparatory training on DKV perspectives, descriptive analysis, and formal analysis. Data collection was conducted through a Google Form survey, covering the identification of color, typography, ornamentation, composition, balance, repetition, and grouping. The inclusion criteria required active DKV students who had participated in the training session. Data were thematically analyzed and tabulated by year. The results indicate significant developments in layout, color use, typography, and the diversity of Malay cultural ornaments. The 2022 poster tended to be asymmetrical and heavily populated with dancer elements; the 2023 poster introduced more balanced compositions with clearer groupings; and the 2024 poster highlighted systematic visual structures, ornament harmony, and emphasis on guest star figures. All posters consistently displayed Malay motifs, although variations in ornament “density” remained evident. Overall, the “Kenduri Seni Melayu” posters from 2022 to 2024 demonstrate a positive evolution in visual structure, layout, and cultural identity consistency. Further improvements are needed in ornament arrangement and information grouping to optimize the effectiveness of visual communication in future designs